Pilocytic Astrocytoma-Derived Cells in Peripheral Blood: A Case Report - Volpentesta, Giorgio; Donato, Giuseppe; Ferraro, Elisabetta; Mignogna, Chiara; Radaelli, Riccardo; Sabatini, Umberto; La Torre, Domenico; Malara, Natalia (Frontiers in Oncology, 2021)
Imaging limitations, invasive tissue biopsies and poor information over the course of treatment to evaluate ‘real-time’ tumor dynamics justify the emerging use of liquid biopsies in the field of brain tumors. Circulating tumor cells (CTCs) from high-grade astrocytomas might reach the circulation by crossing the blood–brain barrier. Here, for the first time, CTCs cytology in a case of pylocitic astrocytoma is described. An obstructive hydrocephalous due to a lateral mesence-phalic tectum mass occluding the Silvio Aqueduct was diagnosed in a young, 18 years old, male. Considering the location of the tumour and the rapid deterioration of the neurological status, it has been decided to urgency treat the patient with ventriculoperitoneal shunting. Magnetic res-onance imaging showed a nodular shaped lesion localized within the left lateral mesencephalic tectum. Stereotactic biopsy was not approachable due significant risk of neurological conse-quences. The diagnosis was performed by blood sampling, a non-invasive procedure for the pa-tient, in order to provide tumour information. Cytopathological features on detected circulating atypical GFAP positive cells led to pilocytic diagnosis confirmed by the patient’s 68 months outcome.